(untitled) (Bangladesh Journal of Endosurgery, 2013)
Background: Foreign body aspiration is a common cause of pulmonary complications and accidental death in children. A high index of suspicion and an early bronchoscopy are essential for the removal of an aspirated foreign body to prevent morbidity and mortality. Methods: This is a retrospective audit of the cases of aspirated foreign bodies in children up to 15 years of age managed in our unit over a 16-year period from 1st February 1995 to 31st January 2011. Results: There were 37 children with the diagnosis of foreign body aspiration during this period. Twenty-seven of these children resided between 50 and 200 km from our hospital. The age ranged from 14 months to 14 years. Twenty-one of these patients presented with an acute onset of respiratory distress without a history of choking. A radioopaque foreign body was visible only in 13 children. In 14 patients, the chest radiograph was normal. The foreign bodies were removed by rigid bronchoscopy. In 29 out of the 37 children the foreign body was non-food product. One patient had a tension pneumothorax and surgical emphysema which settled with a chest drain. Conclusion: An early bronchoscopy, done by a competent surgeon with a rigid bronchoscope deals effectively with the problem of aspirated foreign body, with minimum morbidity. The ability to safely remove an aspirated foreign body is an essential skill to be acquired as part of the training of paediatric surgeons in the developing world. DOI: http://dx.doi.org/10.11593/bje.2013.0101.0002 Bangladesh Journal of Endosurgery Vol.1(1) January 2013: 4-8